Prognostic and Predictive Biomarkers in Adult and Pediatric Gliomas: Toward Personalized Treatment - Haynes, Harry R.; Camelo-Piragua, Sandra; Kurian, Kathreena M. (Frontiers in Oncology, 2014)
It is increasingly clear that both adult and paediatric glial tumour entities represent collections of neoplastic lesions, each with individual pathological molecular events and treatment responses. In this review we discuss the current prognostic biomarkers validated for clinical use or with future clinical validity for gliomas. Accurate prognostication is crucial for managing patients as treatments may be associated with high morbidity and the benefits of high risk interventions must be judged by the treating clinicians. We also review biomarkers with predictive validity which may become clinically relevant with the development of targeted therapies for adult and paediatric gliomas.